Beyond the Guestroom: Financial and Promotional Dimensions of Eco-Friendly Rural Hospitality in Agricultural Landscapes - Vujko, Aleksandra; Mandić, Dušan; Panić, Aleksa; Obradović, Maja; Obradović, Ana; Savić, Ilija; Brdar, Ivana (Agriculture (Basel), 2025)
This study explores sustainable rural tourism entrepreneurship within the Urlaub am Bauernhof (UaB) cooperative network in Austria, offering an integrated model that unites financial, social, environmental, institutional, and marketing dimensions. Employing exploratory factor analysis (EFA) and Structural Equation Modeling (SEM) on data from 393 farm-based accommodation stakeholders, this research identifies sustainable entrepreneurship as comprising six interconnected dimensions: Economic Resilience and Diversification, Sociocultural Integration, Environmental and Regional Commitment, Market Visibility and Strategic Communication, Quality Assurance and Institutional Support, and Perceived Value and Branding. This multidimensional and hierarchically structured framework reflects the complex yet coherent nature of sustainability-driven entrepreneurship in cooperative tourism networks. The findings confirm the multidimensional nature of sustainable entrepreneurship and support the hypothesized structural relationships. The UaB network is presented as a transferable model that demonstrates how cooperative frameworks can enhance sustainability, regional identity, and rural revitalization, offering valuable insights and practical guidance for rural regions in the Western Balkans, where economic challenges, depopulation, and underdeveloped tourism infrastructure prevail. By illustrating a successful cooperative approach rooted in sustainability and regional identity, this study contributes to policy-making aimed at fostering resilient, culturally rich, and environmentally responsible rural tourism entrepreneurship in transitioning contexts.